Agro-physiological assessment of weed interference in groundnut (Arachis hypogea L.) at Sub-Himalayan hill region of Meghalaya - Korav, Santosh; Ram, Vishram; Krishnappa, R; Premaradhya, N (Bangladesh Journal of Botany, 2020)
Field experiment was carried out during Kharif and Rabi seasons of 2016-17 at the mid altitudes of Meghalaya in the precincts of Sub Himalayan hill region to assess and quantify the extent of weed interference on growth and physiology of groundnut in both seasons of the year. Crop physiological parameters viz., LAI, CGR, RGR, NAR, SPAD value, leaf thickness, specific leaf area, specific leaf weight and partitioning efficiency which are key for determining growth and yield of crop were documented periodically. The highest values of all the physiological attributes were found in weed free check, and lowest with weedy check. As weeds, biological agents with similar cellular and plant structure equally affect the crop in all sectors of growth and reproduction but it is not shared uniformly across all stages of crop growth but with increasing period of weed interference decrease the extent of damage to crop plants.